PENGEMBANGAN WILAYAH MELALUI PUSAT PERTUMBUHAN EKONOMI PADA SEKTOR PERTANIAN DI KABUPATEN PINRANG - Muhammad Anugerah Rustan; Fitriani Fitriani; Darmawan Darmawan (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2026)
This study aims to analyze the potential of the agricultural sector as a growth center for economic development in Pinrang Regency, evaluate its impact on farmers' welfare and the regional economy, and formulate strategies and policies to support sustainable regional development through agriculture. This research employs a descriptive qualitative approach to provide a detailed depiction of phenomena without manipulating the involved variables. Data collection techniques include observation, semi-structured interviews, and documentation to obtain in-depth information regarding agricultural conditions in Pinrang Regency. Data analysis is conducted in three main stages: data reduction, data presentation, and conclusion drawing and verification. Data reduction involves filtering relevant information, while data presentation is conducted in a descriptive narrative to identify patterns and relationships. The final step is drawing conclusions, which are verified with theories and collected data. The study results indicate that the agricultural sector in Pinrang Regency has significant potential as an economic driver, with key commodities such as rice, corn, cocoa, coconut, and coffee. Although rice remains the dominant commodity, challenges such as production fluctuations due to weather conditions, policies, and infrastructure remain major obstacles. The government plays a crucial role in supporting this sector through irrigation development and improving market access. To enhance competitiveness and farmers' welfare, agricultural modernization, commodity diversification, and the development of processing industries are essential. The sustainability of the agricultural sector in Pinrang Regency depends on the synergy between the government, the private sector, and the community in fostering sustainable agriculture-based economic growth.